An accurate forearm EMG signal classification method using two-channel electrode - Sueaseenak, Direk; Chanwimalueang, Theerasak; Pintavirooj, Chuchart; Sangworasil, Manas (My University, 2013)
An accurate electromyography (EMG) classification algorithm to control a virtual hand prosthesis with 12 degrees of freedom using two surface EMG electrodes is presented in this paper. We propose the application of independent component analysis (ICA) for blind-source separation of the EMG signals obtained from two electrodes. One of the problems affecting the EMG classification accuracy is the location dependence of the EMG signal due to the superposition of signals from multiple sources. ICA is used to separate the two signals obtained from two surface electrodes into two independent EMG signals prior to the feature extraction and classification processes. We demonstrate that the EMG classification accuracy can be improved using the ICA algorithm. We also propose a novel eigen-based feature that is extracted from the short-time Fourier transform (STFT) magnitude spectrum. Our new feature not only decreases feature dimensions but also performs better than other well-known features. We also implement the EMG classification scheme on the virtual robot arm. The performance shows promising result as indicated by a decrease in the Davies-Bolden (DB) index after applying the ICA. © 2013 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.
Keywords: Eigen-based feature extraction; Electromyogram (EMG); Independent component analysis; Time-frequency analysis